Understanding the Impact of Cultivar, Seed Origin, and Substrate on Bacterial Diversity of the Sugar Beet Rhizosphere and Suppression of Soil-Borne Pathogens - Wolfgang, Adrian; Zachow, Christin; Müller, Henry; Grand, Alfred; Temme, Nora; Tilcher, Ralf; Berg, Gabriele (Frontiers in Plant Science, 2020)
The rhizosphere microbiome is crucial for plant health, especially for preventing roots from being infected by soil-borne pathogens. Microbiota-mediated pathogen response in the soil-root interface may hold the key for microbiome-based control strategies of phytopathogens; we used the pathosystem sugar beet – late sugar beet root rot caused by Rhizoctonia solani in an integrative design and methods comprising in vitro, and in vivo (greenhouse and field) trials to find evidence. Bacterial communities of five different cultivars with different degrees of susceptibility towards R. solani, and different microhabitats (seeds, roots grown under different conditions) using 16SrRNA amplicon analysis were compared. We found cultivar- and microhabitat-specific amplicon sequences variants (ASV) as well as a seed core microbiome shared between all sugar beet cultivars (121 ASVs representing 80-91% relative abundance). In general, cultivar-specific differences in the bacterial communities were more pronounced in seeds than in roots. Seeds of Rhizoctonia-tolerant cultivars contain a higher relative abundance of the genera Paenibacillus, Kosakonia and Enterobacter, while Gaiellales, Rhizobiales and Kosakonia were enhanced in responsive rhizospheres. Analysis of variance revealed the factor ‘Rhizoctona tolerance’ to have a bigger impact (R2 = 0.102) on the bacterial root communities than cultivar-dependent differences (R2 = 0.023). Interestingly, the signature of Pseudomonas poae Re*1-1-14, a well-studied sugar-beet specific biocontrol agent, was frequently found and in higher relative abundances in Rhizoctonia-tolerant than in susceptible cultivars. For microbiome management, we introduced microbial inoculants (consortia) and microbiome transplants (vermicompost) in greenhouse and field trials; both can modulate the rhizosphere and mediate tolerance towards late sugar beet root rot. Our findings suggest that breeding for Rhizoctonia resistance changed the seed microbiota, and both seeds and soil provide specific beneficial bacteria for rhizosphere assembly and microbiota-mediated pathogen tolerance. This can be translated into microbiome management strategies for plant and ecosystem health.